2016
DOI: 10.1186/s12906-016-1183-0
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo model exhibits protective effects of sesamin against destruction of cartilage induced with a combination of tumor necrosis factor-alpha and oncostatin M

Abstract: BackgroundRheumatoid arthritis (RA) is an autoimmune disease associated with chronic inflammatory arthritis. TNF-α and OSM are pro-inflammatory cytokines that play a key role in RA progression. Thus, reducing the effects of both cytokines is practical in order to relieve the progression of the disease. This current study is interested in sesamin, an active compound in sesame seeds. Sesamin has been shown to be a chondroprotective agent in osteoarthritis models. Here, we have evaluated a porcine cartilage expla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 37 publications
(60 reference statements)
0
8
0
Order By: Relevance
“…138181) were approved by the National Park, Wildlife and Plant Conservation Department, Ministry of Natural Resources and Environment, Bangkok, ailand. Sesamin was prepared as previously described according to Phitak's and Kansai's reports [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…138181) were approved by the National Park, Wildlife and Plant Conservation Department, Ministry of Natural Resources and Environment, Bangkok, ailand. Sesamin was prepared as previously described according to Phitak's and Kansai's reports [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Sesamin also efficiently relieves pathological progression in the model of IL-1β-induced osteoarthritis (OA) [29]. Moreover, our previous study demonstrated a protective effect of sesamin against a cartilage degradation model induced by TNF-α and OSM [31]. On the strength of this evidence, it is possible that sesamin also inhibits cytokine production in inflammatory processes in synovitis caused by RA progression.…”
Section: Introductionmentioning
confidence: 99%
“…Results of this research indicated that hs‐CRP and TNF‐α in sesamin group decreased significantly in the end of study. The activity of some of the proinflammatory cytokines such as interleukin‐1β (IL‐1β), interleukin‐6 (IL‐6), interleukin‐8 (IL‐8), and granulocyte‐monocyte colony‐stimulating factor is enhanced by the paracrine character of TNF‐α (Khansai, Boonmaleerat, Pothacharoen, Phitak, & Kongtawelert, ). In particular, increased amounts of these proinflammatory cytokine products in RA joints promote the up‐regulation of degrading enzymes at the site of inflammation.…”
Section: Discussionmentioning
confidence: 99%